#TITLE_ALTERNATIVE# - SENO RESPATI PARLINTO (NIM : 12208059), PRADHIPTA
This study was conducted by creating a numerical model to analyzing the effect of linier discontinuity near vertical well to area estimation. The analysis will be performed by observing influence of the distance of linier discontinuity to estimating area of reservoir using pseudo steady-state analysis and derivative analysis on well testing. The problem in this study is limited only by the variation in the distance of discontinuities to well. The results of this study indicate that the discontinuity influence the estimated value of the area. The influence of discontinuity is decreasing as a function of increasing distance discontinuity from well. Those could seen on numerical calculation. Therefore, there found the reservoir with a big area, but the well testing result was disappointed, we can say that the reservoir has discontinuity.